Malcolm X : inventing radical judgment - Terrill, Robert (Rhetoric and public affairs series., 2007)
"Malcolm X, like any orator, did not fashion his discourse in a vacuum but worked within and modified modes fashioned by his predecessors. Malcolm X: Inventing Radical Judgment begins by exploring the interpretive strategies presented in key texts from the history of African American protest, establishing a spectrum against which Malcolm's oratory can be assessed. Then the texts of speeches that Malcolm delivered while he was a minister for the Nation of Islam and the texts of speeches and statements he made after he left the Nation are analyzed carefully to discern the strategies of interpretation and judgment that he enacted and fostered in his audiences. Finally, this radical judgment, presented in and through Malcolm's public discourse, is recontextualized by using three disparate theoretical approaches. The purpose of this triangulation is not to contain the rhetoric of Malcolm X within the limitations of these vocabularies, but rather to show that the changing potential of Malcolm's rhetoric lies, in part, in its iconoclastic refusal to be constrained by definitive boundaries."--Jacket.